Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(x-y\right)^2\left(z^2-2z+1\right)-2\left(z-1\right)\left(x-y\right)^2+\left(x-y\right)^2\)
\(A=\left(x-y\right)^2\left(z-1\right)^2-2\left(x-y\right)\left(z-1\right)\left(x-y\right)+\left(x-y\right)^2\)
\(A=\left[\left(x-y\right)\left(z-1\right)-\left(x-y\right)\right]^2\ge0\) \(\forall x,y,z\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 :
a ) \(z\left(y-x\right)+y\left(x-z\right)+x\left(y+z\right)-2yz+100\)
\(=yz-xz+xy-yz+xy+xz-2yz+100\)
\(=2xy-2yz+100\) ( Đề sai )
b ) \(2y\left(y^2+y+1\right)-2y^2\left(y+1\right)-2\left(y+10\right)\)
\(=2y^3+2y^2+2y-2y^3-2y^2-2y-20\)
\(=-20\)
Vậy biểu thức không phụ thuộc vào biến .
Bài 2 :
a ) \(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)
\(\Leftrightarrow36x^2-12x-36x^2+27x=30\)
\(\Leftrightarrow15x=30\)
\(\Leftrightarrow x=2\)
b ) \(2x\left(x-5\right)-x\left(2x+3\right)=x^2-x\left(x-1\right)\)
\(\Leftrightarrow2x^2-10x-2x^2-3x-x^2+x^2-x=0\)
\(\Leftrightarrow-14x=0\)
\(\Leftrightarrow x=0\)